Band alignment and charge transfer pathway in three phase anatase-rutile-brookite TiO2 nanotubes: an efficient photocatalyst for water splitting - Preethi, L. K.; Mathews, Tom; Nand, Mangla; Jha, S. N.; Chinnakonda, Gopinath S.; Dash, Sitaram (Applied Catalysis B-Environmental, 2017)
The study reports electrochemical synthesis, phase evolution and hydrogen generation efficiency of anatase, anatase-rutile and anatase-rutile-brookite (ARB) TiO2 nanotubes for the first time. The SEM and TEM micrographs confirm the tubular morphology of the samples. The presence of anatase, rutile and brookite phases in a single nanotube is confirmed from high resolution TEM analysis. The water splitting efficiency of the three systems are studied under one sun illumination. It is observed that the anatase-rutile-brookite TiO2 nanotubes are highly efficient compared to anatase-rutile or anatase TiO2 nanotubes. The hydrogen generated by ARB composites, after four hours of one sun illumination, is found to be nearly twice that of anatase TiO2 nanotubes and 1.6 times that of anatase-rutile TiO2 nanotubes. The results suggest that the ARB in single nanotube having two junction interfaces, highly facilitate interparticle charge transfer compared to single junction anatase-rutile or bare anatase TiO2 nanotubes. From the deconvolution of PL spectra and the synchrotron radiation assisted valence band edge analysis, the band diagram for the anatase-rutile-brookite phase is constructed. The charge separation and its transfer pathway for efficient photo-assisted water splitting are delineated. This opens a new route for the simple synthesis and study of tri-phase TiO2 for efficient photocatalytic water splitting compared to the widely studied two phase TiO2. (C) 2017 Published by Elsevier B.V.
Keywords: Anatase-Rutile-Brookite; Hydrogen generation; nanotubes; Photocatalysis; photoluminescence; Valence band edge